Application Of Neutrosophic Soft Set In Medical Diagnosis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fuzzy theory and neutrosophic theory are almost trending in all the fields. This paper exhibit techniques of neutrosophic soft set by demonstrating a case study of the patients. Analyse the medical report of the patients; the result obtained in the current work is compared with the existing earlier result to carry out the conclusion.